Supersymmetric quantum mechanics method for the Fokker-Planck equation with applications to protein folding dynamics - Polotto, Franciele [UNESP]; Drigo Filho, Elso [UNESP]; Chahine, Jorge [UNESP]; Oliveira, Ronaldo Junio de (Elsevier B.V., 2018)
This work developed analytical methods to explore the kinetics of the time-dependent probability distributions over thermodynamic free energy profiles of protein folding and compared the results with simulation. The Fokker-Planck equation is mapped onto a Schrodinger-type equation due to the well-known solutions of the latter. Through a semi analytical description, the supersymmetric quantum mechanics formalism is invoked and the time-dependent probability distributions are obtained with numerical calculations by using the variational method. A coarse-grained structure-based model of the two-state protein TmCSP was simulated at a C-alpha level of resolution and the thermodynamics and kinetics were fully characterized. Analytical solutions from non-equilibrium conditions were obtained with the simulated double-well free energy potential and kinetic folding times were calculated. It was found that analytical folding time as a function of temperature agrees, quantitatively, with simulations and experiments from the literature of TmCSP having the well-known 'U' shape of the Chevron Plots. The simple analytical model developed in this study has a potential to be used by theoreticians and experimentalists willing to explore, quantitatively, rates and the kinetic behavior of their system by informing the thermally activated barrier. The theory developed describes a stochastic process and, therefore, can be applied to a variety of biological as well as condensed-phase two-state systems. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Quantum mechanics; Schrodinger equation; Folding rates; Structure-based model